Novel quinazolinone-based 2, 4-thiazolidinedione-3-acetic acid derivatives as potent aldose reductase inhibitors. (December 2017) - Metwally, Kamel; Pratsinis, Harris; Kletsas, Dimitris; Quattrini, Luca; Coviello, Vito; Motta, Concettina La; El-Rashedy, Ahmed A; Soliman, Mahmoud ES
Aim: Targeting aldose reductase enzyme with 2, 4-thiazolidinedione-3-acetic acid derivatives having a bulky hydrophobic 3-arylquinazolinone residue.Materials & methods: All the target compounds were structurally characterized by different spectroscopic methods and microanalysis, their aldose reductase inhibitory activities were evaluated, and binding modes were studied by molecular modeling.Results: All the synthesized compounds proved to inhibit the target enzyme potently, exhibiting IC50 values in the nanomolar/low nanomolar range. Compound5i (IC50 = 2.56 nM), the most active of the whole series, turned out to be almost 70-fold more active than the only marketed aldose reductase inhibitor epalrestat.Conclusion: This work represents a promising matrix for developing new potential therapeutic candidates for prevention of diabetic complications through targeting aldose reductase enzyme.